Cold atmospheric plasma induces apoptosis of melanoma cells via Sestrin2‐mediated nitric oxide synthase signaling. Issue 1 (7th September 2018) - Xia, Jun; Zeng, Weihui; Xia, Yumin; Wang, Bingchuan; Xu, Dehui; Liu, Dingxin; Kong, Michael G.; Dong, Yingying
Abstract : Cold atmospheric plasma (CAP) represents a promising therapy for selectively cancer killing. However, the mechanism of CAP‐induced cancer cell death remains unclear. Here, we identified the tumor necrosis factor‐family members, especially Fas, and overloaded intracellular nitric oxide participated in CAP induced apoptosis in A375 and A875 melanoma cell lines, which was known as extrinsic apoptosis pathway. This progress was mediated by antagonistic protein of reactive oxygen species, Sestrin2. The over expression of Sestrin2 induced by plasma treatment resulted in phosphorylation of p38 mitogen‐activated protein kinase (MAPK), followed by increased expression of nitric oxide synthase (iNOS), Fas and Fas ligand. Depletion of Sestrin2 reduced iNOS and Fas expression, which was associated with reduction of plasma‐induced apoptosis. In contrast, inhibition of iNOS activity and phosphorylation of p38 did not alter Sestrin2 expression in plasma‐treated melanoma cells. Taken together, cold atmospheric plasma increases Sestrin2 expression and further activates downstream iNOS, Fas and p38 MAPK signaling to induce apoptosis of melanoma cell lines. These findings suggest a previously unrecognized mechanism in melanoma cells response to cold atmospheric plasma therapy. Abstract : CAP generated by S‐DBD plasma device stimulates Sestrin2 expression to activate p38 MAPK signaling in the melanoma cells examined. The downstream effects include the enhancing expression of iNOS, Fas as well as FasL. The enhanced iNOS induces intracellular nitric oxide. Moreover, the uploaded expression of Fas and FasL led to the activation of Caspase 8 and Caspase 3. This is one of the mechanisms revealing CAP induced melanoma cell apoptosis.